Fico Words : Perancangan Game Antarmuka Tebak Kata Interaktif Berbasis Android untuk Anak Usia Dini Mengenal Huruf dan Kata - Ivanka, Abdee Achmad; Firdaus, M. Ersam Babul (Universitas Muhammadiyah Ponorogo, 2024)
Embracing technological advancements, Fico Words presents innovative solutions in the form of customized word guessing games tailored to different age groups of children. The difficulty levels can be adjusted, providing flexibility to customize the learning experience according to each child's developmental stage. The child-friendly design of this application aims to create an environment that supports children's vocabulary comprehension while stimulating their language development. By combining educational elements with fun, Fico Words serves as an interactive learning platform that creates engaging and beneficial learning opportunities. With a commitment to creating effective and entertaining educational solutions, this project reflects the author's dedication to supporting the educational development of children through the use of smart and effective technology. Fico Words is not just a game; it is a positive step towards supporting enjoyable and meaningful learning for the next generation.